Pencemaran Nama Baik Dan Penghinaan Melalui Media Teknologi Informasi Komunikasi Di Indonesia Pasca Amandemen UU ITE - Samudra, Anton Hendrik (Jurnal Hukum & Pembangunan, 2020)
The amendment of the ITE Law is conducted to provide better legal certainty. This is an effort to respond to society development and aims to provide better legal protection and justice. The implementation of freedom of expression in the media of Information Communication Technology (ICT) affecting the number of defamation. With the amendment of ITE law, it is necessary to examine the nature of defamation offense and libel through ICT media.